The Importance of Organizing Cycle Paths in the Center of Yerevan in the Study Processes on Sustainable Mobility - Mashinyan, Astghik (Scientific Papers of National University of Architecture and Construction of Armenia, 2023)
The present work studies the possibilities of organizing bicycle lanes in the city center of, studying the international experience and bringing out the advantages in urban sustainable mobility. The organization of bicycle lanes in the city center of Yerevan is urgently relevant, considering the rapidly developing trend of cycling. The positive effects of revising the existing bicycle lanes and creating new lanes in the city center of Yerevan were discussed in the context of the development of sustainable urban planning. The international experience were studied, and bringed out the most important urban planning norms and their possible integration in the city center of Yerevan, as an overloaded with transport vehicles, road infrastructure and in some cases, also in green areas - gardens, parks. A number of problems arising due to the lack of bicycle paths were also brought out, such as road accidents, incomplete use of alternative means of transportation, carbon dioxide emissions related to the growth of personal vehicles, traffic jams, overloading of city vehicles.